Heme oxygenase-1 in pregnancy and cancer: similarities in cellular invasion, cytoprotection, angiogenesis, and immunomodulation - Zhao, Hui; Ozen, Maide; Wong, Ronald J.; Stevenson, David K. (Frontiers in Pharmacology, 2015)
Pregnancy can be defined as a “permissible” process, where a semi-allogeneic fetus and placenta are allowed to grow and survive within the mother. Similarly, in tumor growth, antigen-specific malignant cells proliferate and evade into normal tissues of the host. The microenvironments of the placenta and tumors are amazingly comparable, sharing similar mechanisms exploited by fetal or cancer cells with regard to surviving in a hypoxic microenvironment, invading tissues via degradation and vasculogenesis, and escaping host attack through immune privilege. Heme oxygease-1 (HO-1) is a stress-response protein that has anti-oxidative, anti-apoptotic, pro-angiogenic, and anti-inflammatory properties. Although a large volume of research has been published in recent years investigating the possible role(s) of HO-1 in pregnancy and in cancer development, the molecular mechanisms that regulate these “yin-yang” processes have still not been fully elucidated. Here, we summarize and compare pregnancy and cancer development, focusing primarily on the function of HO-1 in cellular invasion, cytoprotection, angiogenesis, and immunomodulation. Due to the similarities of both processes, a thorough understanding of the molecular mechanisms of each process may reveal and guide the development of new approaches to prevent not only pregnancy disorders; but also, to study cancer.